PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syafri Yusman; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine effect of profitability, liquidity and leverage on company of basic industry and chemical sectors listed in Indonesia Stock Exchange (IDX). Profitability ratios were used as independent variables is Return On Assets (ROA) and Return On Equity (ROE), the ratio of liquidity are used ad independent variable is Current Ratio (CR) and Leverage ratio were use as independent variables is Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER). While being used as the dependent variables is Dividend Policy measured by Dividend Payout Ratio (DPR) listed in Indonesia Stock Exchange (IDX).Data used in this study is a secondary data, financial reports (annual report). As for data listed in Indonesia Stock Exchange (IDX) for 5 years from 2010 to 2014. Sampling was done by purposive sampling, used are 7 companies. Analysis data using multiple linear regressions analysis, t test, f test and coefficient of determination test. Analysis data using multiple linear regressions analysis with SPSS 21.The analysis showed that the variable profitability does not effect on dividend policy on company of basic industry and chemical sectors listed in the Indonesia Stock Exchange. Liquidity variable does not affect on dividend policy on company of basic industry and chemical sectors listed in the Indonesia Stock Exchange. Whereas leverage variables has effect on dividend policy of basic industry and chemical company listed in the Indonesia Stock Exchange. Simultaneous research results showed has effect of variable profitability, liquidity and leverage on dividend policy on company of basic industry and chemical sectors listed in the Indonesia Stock Exchange.Keywords : Profitability, Liquidity, Leverage, Dividend Policy